Citrus Diseases Exotic to Florida: Huanglongbing (Citrus Greening) - Kuang-Ren Chung; R. H. Briansky (EDIS)
Citrus is susceptible to a large number of diseases caused by plant pathogens. Economic losses due to plant diseases can be severe, but fortunately, not all pathogens attacking citrus are present in Florida. There are other serious, exotic pathogens that have not been introduced into Florida. This paper will discuss Huanglongbing (HLB), also commonly called citrus greening. This document is PP-210, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 2005.